Strategi Pengelolaan Perpustakaan Digital untuk Meningkatkan Akses Informasi Masyarakat di Dinas Kearsipan dan Perpustakaan Daerah Kebumen - Nachroy, Faiq Ali; Murtopo, Bahrun Ali (IAINU Kebumen, 2025)
The development of information technology drives the transformation of digital libraries as a primary means to improve public access to information, especially for students. In Kebumen Regency, the Regional Archives and Library Office (Disarpus) has developed a digital library in collaboration with vendors such as Digido, Kubuku, and the internal platform I Kebumen. This study aims to analyze the strategies for managing digital libraries, supporting and inhibiting factors, and efforts to increase public access to information. The research employed observation, interviews, and documentation to gather data on the implementation of digital services. The results indicate that supporting factors include government policy support, competent young human resources, strategic location, collaboration with vendors, and adequate digital infrastructure. Inhibiting factors involve low digital literacy, limited collections, complex login and navigation, and dependence on third-party vendors. Strategies to enhance access include staff training, digital content diversification, infrastructure upgrades, promotion through literacy ambassadors and social media, and routine evaluations based on public feedback. The study concludes that with integrated strategies and sustained policy support, Disarpus Kebumen has the potential to become a pioneer in effective digital library management.